2020
DOI: 10.1111/1751-7915.13559
|View full text |Cite
|
Sign up to set email alerts
|

The potential use of the Penicillium chrysogenum antifungal protein PAF, the designed variant PAFopt and its γ‐core peptide Pγopt in plant protection

Abstract: The prevention of enormous crop losses caused by pesticide-resistant fungi is a serious challenge in agriculture. Application of alternative fungicides, such as antifungal proteins and peptides, provides a promising basis to overcome this problem; however, their direct use in fields suffers limitations, such as high cost of production, low stability, narrow antifungal spectrum and toxicity on plant or mammalian cells. Recently, we demonstrated that a Penicillium chrysogenum-based expression system provides a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 52 publications
2
29
1
Order By: Relevance
“…So far, no adverse effects of the fungal APs and PDs on plants or fruits have been reported in the literature (Vila et al, 2001;Moreno et al, 2003Moreno et al, , 2006Theis et al, 2005;Barakat, 2014;Garrigues et al, 2018); however, little information is available on the induction of morphological aberrations when growing seedlings with these biomolecules. Exceptions are AFP that did not affect the growth of the tomato plant roots (Theis et al, 2005) or PAF and its derived variant and PD that did neither harm the leaves of barley (Barna et al, 2008) nor those of tomatoes nor affected the seedlings of M. truncatula (Tóth et al, 2020). In the present study, the vegetative growth and the morphology of the roots of the M. truncatula seedlings were not disturbed by NFAP (Figure 4).…”
Section: Discussioncontrasting
confidence: 46%
See 4 more Smart Citations
“…So far, no adverse effects of the fungal APs and PDs on plants or fruits have been reported in the literature (Vila et al, 2001;Moreno et al, 2003Moreno et al, , 2006Theis et al, 2005;Barakat, 2014;Garrigues et al, 2018); however, little information is available on the induction of morphological aberrations when growing seedlings with these biomolecules. Exceptions are AFP that did not affect the growth of the tomato plant roots (Theis et al, 2005) or PAF and its derived variant and PD that did neither harm the leaves of barley (Barna et al, 2008) nor those of tomatoes nor affected the seedlings of M. truncatula (Tóth et al, 2020). In the present study, the vegetative growth and the morphology of the roots of the M. truncatula seedlings were not disturbed by NFAP (Figure 4).…”
Section: Discussioncontrasting
confidence: 46%
“…As for the harmlessness in humans and animals, our proof-of-principle experiments indicated that NFAP and the PD γ NFAP -opt were not cytotoxic against keratinocytes, colonic epithelial cells, and monocytes and were not hemolytic in the antifungal effective concentration (Figure 3). Therefore, this N. fischeri protein and peptide exhibited harmless activity in vitro similar to other members of the fungal APs, such as PAF and AFP (Szappanos et al, 2005(Szappanos et al, , 2006Tóth et al, 2020), PAF γ-core PDs (Sonderegger et al, 2018;Tóth et al, 2020), and NFAP2 (Kovács et al, 2019). Importantly, experiments with a murine model for pulmonary fungal infection and fungal vulvovaginitis further proved the safety in vivo for PAF (Palicz et al, 2013(Palicz et al, , 2016 and NFAP2 (Kovács et al, 2019), respectively.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations